Evaluating Potential QT Effects of JNJ‐54861911, a BACE Inhibitor in Single‐ and Multiple‐Ascending Dose Studies, and a Thorough QT Trial With Additional Retrospective Confirmation, Using Concentration‐QTc Analysis. (5th March 2018) - Timmers, Maarten; Sinha, Vikash; Darpo, Borje; Smith, Brian; Brown, Randy; Xue, Hongqi; Ferber, Georg; Streffer, Johannes; Russu, Alberto; Tritsmans, Luc; Solanki, Bhavna; Bogert, Jennifer; et al.
Abstract: Nonclinical assays with JNJ‐54861911, a β‐secretase 1 inhibitor have indicated that at high concentrations, it may delay cardiac repolarization. A 4‐way crossover thorough QT (TQT) study was performed in 64 healthy subjects with 50 and 150 mg JNJ‐54861911 once daily for 7 days, placebo, and 400 mg moxifloxacin. Retrospective high‐precision QT (HPQT) analysis was performed on serial elecrocardiograms extracted from first‐in‐human single‐ascending dose (SAD) and multiple‐ascending dose (MAD) studies to evaluate if early studies could detect and predict QT effect. In the TQT study, a high therapeutic 50 mg dose did not cause QT prolongation, and an effect >10 milliseconds could be excluded at all postdose timepoints. QT prolongation with peak effect on placebo‐corrected change from baseline QTcF of 15.5 milliseconds (90%CI, 12.9‐18.1 milliseconds) was observed following a supratherapeutic dose (150 mg). No clinically relevant QT changes were observed in earlier studies. However, with SAD/MAD findings by HPQT, the slope of the exposure–response (ER) relationship in the SAD study (doses up to 150 mg) was similar to the TQT study slope, and the estimated QT effect was comparable at high plasma levels. In the MAD study, doses up to 90 mg once daily for 7 days resulted in JNJ‐54861911 peak plasma concentrations (Cmax ) comparable to those in the SAD study (∼750 ng/mL), but ER by HPQT failed to detect a QT effect and resulted in negative estimations. Adding a higher dose cohort (150 mg; Cmax, 1125 ng/mL) demonstrated a QT effect, with a slightly lower ER slope than the TQT study. JNJ‐54861911 (up to 50 mg) did not cause QT prolongation at clinically relevant plasma concentrations in any studies. Provided sufficiently high plasma concentrations were captured, mild QT prolongation observed postdose with a supratherapeutic dose could be detected (TQT study) and estimated in SAD/MAD studies. Based on population pharmacokinetic modeling and simulation, 5 and 25 mg doses are currently considered for further phase 3 studies and are expected not to cause any relevant QT prolongation.